Aspectos eco-socioeconômicos do cultivo do café sombreado na serra de Baturité, Ceará, Brasil - Ribeiro, Sofia Regina Paiva (2023)
The Residual Massif of Baturité, known as Serra de Baturité, a formation of the Brazilian relief located in the northeastern semi-arid region, is home to a rich phyto-faunistic biodiversity, which includes forest remnants of the Atlantic Forest, a biome rich in diversity. Two centuries ago (1822-2022), in this humid enclave, in the middle of the hinterlands of Ceará, an agricultural activity began that brought economic and environmental impact: coffee growing. Today, the coffee produced in the mountainous region of Baturité is appreciated for being 100% Arabic, shaded, free of agrochemicals and for having preservationist identity and productive characteristics. In view of the above, the present research aims to analyze and discuss the contribution of ecologically based coffee farming to environmental preservation and socioeconomic development in the mountainous region of the municipality of Baturité, Ceará. Therefore, the impact of the revitalization of coffee production will be considered, based on actions aimed at sustainable tourism associated with the singularities of regional shade coffee. He presentation of the analyzes was structured in four chapters. The first aimed to analyze the eco-socioeconomic impact of the implementation of the Baturité APA in the last five years (2015–2020). The second aimed to measure the eco-socioeconomic impacts of shaded and agroecological coffee growing in the municipality of Baturité, Ceará, Northeastern Brazil. The objective of the third was to analyze the role of women as a social actor in the coffee production process in the Serra de Baturité, state of Ceará, considering the historical-cultural, socioeconomic, and environmental aspects. The last chapter aimed to verify the impact of the revitalization of the shade coffee culture in the Baturité mountain range from initiatives aimed at tourism, environmental preservation, and regional socioeconomic development. The study includes theoretical-methodological criteria of a qualitative, descriptive and exploratory nature, comprising bibliographic research (primary and secondary sources), semi-structured interviews and participant observation. The empirical research was carried out with key sources in Baturité, covering public and/or private institutions that have a direct or indirect relationship with coffee growing in the region, and in the rural mountain communities of Olho d’Água and Uirapuru. The universe to be researched to obtain the sample for the experiment in focus comprises twenty key sources, among small family-based rural producers, coffee growers, entrepreneurs, traders, tourists, and people with high historical, cultural, social and environmental knowledge about production. of the region's shade coffee. The temporal cut comprises the triennium 2021 to 2023, considering different temporalities for the bibliographic study. It can be inferred that the unique characteristics of mountain coffee farming associated with the region's tourist potential have been reflected in public and private actions and interventions, with the aim of strengthening and/or revitalizing the production of shade coffee, tourism aimed at rural areas. , the creative and circular economy and rural entrepreneurship, with emphasis on the female presence, positively impacting the local economy, as well as socio- environmental preservation. The data indicate that, despite the woman/coffee farmer performing multiple functions (productive, entrepreneurship, marketing, and tourism) and contributing to the economic, sociocultural and environmental development of Serra de Baturité, she is marginalized or in a hierarchically inferior position to the man/coffee farmer, which reinforces the gender asymmetries present in rural, social and academic historiography. It can be inferred that the “third wave of coffee” movement has contributed strongly to the dissemination, valorization, and revitalization of shade coffee, as well as to sustainable territorial development and the valorization of social memory (local identity).